Clinical effectiveness and safety of sirolimus in pediatric patients with complex vascular anomalies: necessitating personalized and comprehensive approaches - Kim, Minji; Hong, Kyung Taek; Park, Hyun Jin; Kim, Bo Kyung; Choi, Jung Yoon; Kim, Hyun-Young; Kang, Hyoung Jin (Frontiers in Pediatrics, 2023)
Background: Managing complex vascular anomalies in pediatric care requires comprehensive approaches. Sirolimus, an mTOR inhibitor with immunosuppressive and anti-angiogenic properties, offers promise. We evaluated sirolimus's effectiveness and safety in pediatric patients with complex vascular anomalies at a tertiary children's hospital.Methods: Our study included 20 patients, aged 1 month to 19 years, with diverse vascular anomalies resistant to conventional therapies or located in high-risk areas precluding surgery. The evaluation of response encompassed measuring the reduction in the size of the targeted vascular or lymphatic lesions as observed on radiologic imaging, along with considering improvements reported by the patients.Results: Patients used sirolimus for a median of 2.1 years, ranging from 0.6-4.3 years. Results indicated that 60% of patients achieved complete or partial response (CR/PR), whereas 40% had stable disease (SD). Notably, no disease progression occurred. Lesion size assessment was complex, yet patients' self-reported improvements were considered. Three patients reinitiated sirolimus after discontinuation due to worsening lesions. Sirolimus treatment demonstrated good tolerability, with minor complications except for one case of Pneumocystis jiroveci pneumonia. Group comparisons based on response highlighted better outcomes in patients with vascular tumors (CR/PR group 58.0% vs. SD group 0.0%, P=0.015) or localized measurable lesions (83.3% vs. 12.5%, P=0.005).Our study underscores sirolimus's potential for treating complex vascular anomalies in pediatric patients. Challenges associated with optimal treatment duration and concurrent interventions necessitate a comprehensive approach and genetic testing to optimize outcomes.